2006
DOI: 10.1104/pp.106.081703
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Ubiquitin/Proteasome Pathway in Pollen Tube Growth with Emphasis on MG132-Induced Alterations in Ultrastructure, Cytoskeleton, and Cell Wall Components

Abstract: The ubiquitin/proteasome pathway represents one of the most important proteolytic systems in eukaryotes and has been proposed as being involved in pollen tube growth, but the mechanism of this involvement is still unclear. Here, we report that proteasome inhibitors MG132 and epoxomicin significantly prevented Picea wilsonii pollen tube development and markedly altered tube morphology in a dose-and time-dependent manner, while hardly similar effects were detected when cysteineprotease inhibitor E-64 was used. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 57 publications
(89 reference statements)
7
77
1
1
Order By: Relevance
“…50 The importance of the selective proteolytic activity associated with 26S proteasome system during pollen germination and tube growth was repeatedly demonstrated. [51][52][53] Moreover, a number of transcripts encoding proteasome-associated and F-box proteins were identified in Arabidopsis developing and germinating pollen. 42,54 Proteasomes were also demonstrated to perform other nonproteolytic functions including transcriptional regulation, [55][56][57] RNase activity, 58,59 translational regulation, 60,61 and possessing cytoskeleton-binding properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The importance of the selective proteolytic activity associated with 26S proteasome system during pollen germination and tube growth was repeatedly demonstrated. [51][52][53] Moreover, a number of transcripts encoding proteasome-associated and F-box proteins were identified in Arabidopsis developing and germinating pollen. 42,54 Proteasomes were also demonstrated to perform other nonproteolytic functions including transcriptional regulation, [55][56][57] RNase activity, 58,59 translational regulation, 60,61 and possessing cytoskeleton-binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…42,54 Proteasomes were also demonstrated to perform other nonproteolytic functions including transcriptional regulation, [55][56][57] RNase activity, 58,59 translational regulation, 60,61 and possessing cytoskeleton-binding properties. 52,62 With regard to all abovementioned alternative functions, the presence of proteasome subunits within EPP complexes is natural in relation to complex EPP-associated spatially and temporarily regulated activities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using MG132 have shown that the UPS is involved in the regulation of plant cell microtubule (MT) networks (Yanagawa et al, 2002;Oka et al, 2004;Sheng et al, 2006;S. Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen grains were kept at room temperature for 30 min and then suspended in the germination medium containing 12% Suc, 0.01% H 3 BO 3 , and 0.01% CaCl 2 at pH 6.8 as documented previously (Sheng et al, 2006). All of the samples were incubated on a shaker (121 rpm) at 24°C in the dark.…”
Section: Plant Materials and Growthmentioning
confidence: 99%